2022
DOI: 10.1186/s13567-022-01102-4
|View full text |Cite
|
Sign up to set email alerts
|

Species identification by MALDI-TOF MS and gap PCR–RFLP of non-aureus Staphylococcus, Mammaliicoccus, and Streptococcus spp. associated with sheep and goat mastitis

Abstract: Staphylococci and streptococci are common causes of intramammary infection in small ruminants, and reliable species identification is crucial for understanding epidemiology and impact on animal health and welfare. We applied MALDI-TOF MS and gap PCR–RFLP to 204 non-aureus staphylococci (NAS) and mammaliicocci (NASM) and to 57 streptococci isolated from the milk of sheep and goats with mastitis. The top identified NAS was Staphylococcus epidermidis (28.9%) followed by Staph. chromogenes (27.9%), haemolyticus (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
(68 reference statements)
0
32
0
1
Order By: Relevance
“…Str. parauberis is associated with small ruminant mastitis and has been identified as a minor component of cheeses produced with their milk [ 38 , 58 , 59 ]. Other mastitis-causing pathogens can be found in cheese via contaminated milk [ 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Str. parauberis is associated with small ruminant mastitis and has been identified as a minor component of cheeses produced with their milk [ 38 , 58 , 59 ]. Other mastitis-causing pathogens can be found in cheese via contaminated milk [ 60 , 61 , 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…genera in preserved boar semen, we used only the classic and Miniapi methods. According to studies in the literature [ 34 ], the Conventional Identification (CI)-MiniApi method compared to MALDI-TOF [ 35 , 36 ] or MT-MS is slower and less faithful but generates the same results. According to Sendid B. et al (2013), concordance between the two techniques is excellent for the medically important species (98–100%), including the identification of closely-related species ( Candida genus).…”
Section: Discussionmentioning
confidence: 99%
“…Non- aureus staphylococci (NAS) are abundant in dairy cows’ teat apices that are recovered from bovine fecal samples, and their differences in ecology, epidemiology, effect on udder health, and virulence or protective traits have been reported among other species within this group (De Visscher et al 2016 ; Vanderhaeghen et al 2015 ; Wuytack et al 2020a , b ). Several studies have reported that S. chromogenes, S. epidermidis, S. xylosus , S. vitulinus , S. simulans , and M. sciuri are the main NASM species isolated from the tips and skin of the animal’s teats increasing the probability to develop an intramammary infection during lactation, whereas in milk samples, S. chromogenes , S. xylosus , S. haemolyticus are most prevalent (Koop et al 2012 ; Rosa et al 2022 ; Ruiz-Romero et al 2020 ; Traversari et al 2019 ). Overall, more NASM isolates are identified in used bedding than in unused bedding (Adkins et al 2022 ).…”
Section: Non- Aureus Staphylococci and Mammaliicoccimentioning
confidence: 99%